Feminist international relations : an unfinished journey - Sylvester, Christine, 1949- (Cambridge studies in international relations ;, 2002)
Christine Sylvester examines the history of feminists' efforts to include gender relations in the study of international relations. Tracing the author's own 'journey' through the subject, the book examines theories, methods, people and locations which have been neglected by conventional scholarship.